Faktor-Faktor yang Memengaruhi Stress pada Anak Thalasemia Bergantung Transfusi - Munifah, Laelatul; Agsutini, Nur; Rachmawati, Imami Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the factors influencing stress in children with transfusion-dependent thalassemia. The method used in writing this article is a systematic review. This article was written using a database owned by the University of Indonesia through lib. UI is a website that facilitates students' search for literature. Eight databases were used to write the systematic review in this article, namely Proquest, ScienceDirect, Pubmed, Scopus, EMBASSE, EBSCO, Taylor & Francis Online, and SpringerLink, and used the